Academic stress and the academic performance of students in a education institute - Infantas Vela, Sol María (2023)
The objective of the study was to determine the relationship between academic stress and academic performance of the students of the Edutek Private Pedagogical Higher Education Institute of the city of Tacna in the year 2021. For this, the research was of a basic type according to its purpose, of nature quantitative, synchronous in scope, non-experimental and cross-sectional design, and correlational level, aimed at a population of 181 students, and a sample of 133 students. It was concluded that the academic stress and the academic performance of the students of the Edutek Private Pedagogical Higher Education Institute of the city of Tacna in the year 2021 are significantly related, having demonstrated the correlation between both variables according to the results of the Rho-Spearman test, with a significance value less than 0.05, and whose correlation coefficient, when negative, shows an inverse and moderate relationship, that is, as academic stress is lower, academic performance in consequence is higher, and vice versa.